Bat Algorithm for Solving Dynamic Economic Emission Dispatch Problem - Hardiansyah, Hardiansyah (Indonesian Journal of Electrical Engineering and Informatics (IJEEI), 2018)
This paper proposes a new meta-heuristic search algorithm, called Bat Algorithm (BA). Bat algorithm is an optimization technique motivated by the echolocation behavior of natural bats in finding their foods. The proposed algorithm is presented to solve the dynamic economic emission dispatch (DEED) problem. As emission minimization is conflicting with minimum cost of generation, the DEED problem becomes a multi-objective optimization problem with conflicting objectives. The proposed algorithm is validated on 5-unit generation system for a 24 h time interval. The results proved the efficiency of the proposed method when compared with the other optimization algorithms reported in the literature.